Predicting adolescents’ safe food handling using an extended theory of planned behavior - Mullan, Barbara; Wong, C.; Kothe, E. (Pergamon, 2013)
The aim of this study was to investigate whether the Theory of Planned Behavior (TPB) with the addition of risk perception could predict safe food handling in a sample of adolescents from the UK and Australia over and above the explanatory power of knowledge. It was hypothesized that knowledge would predict both intention to prepare food safely and self-reported food hygiene behavior. It was expected that attitudes, subjective norm, perceived behavioral control and risk perception would predict intentions over and above knowledge. It was hypothesized that intentions and PBC would significantly predict food hygiene behavior over and above the influence of knowledge. Participants were recruited from secondary schools in Australia and the UK (n = 205). Knowledge alone predicted 4% of intention and 1.4% of behavior. TPB variable with the addition of risk perception accounted for an additional 60% of the variance in intention. PBC and intention accounted for an additional 24% of the variance in behavior. Knowledge was not a significant predictor of intention or behavior once other variables were added to the model these results provide further support for criticisms of interventions that have targeted food safety through knowledge based interventions. The results provide further support for the utility of the TPB in predicting safe food handling. The addition of risk perception added to the predictive utility of the model, suggesting that researchers may want to incorporate that factor into future considerations of food hygiene using the TPB.